Experimental data on novel Fe(III)-complexes containing phenanthroline derivatives for their anticancer properties - Matos, Cristina P.; Adiguzel, Zelal; Yildizhan, Yasemin; Cevatemre, Buse; Bagci-Onder, Tugba; Cevik, Ozge; Nunes, Patrique; Ferreira, Liliana P.; Carvalho, Maria Deus; Campos, Débora L. [UNESP]; Pavan, Fernando R. [UNESP]; Pessoa, João Costa; et al. (Elsevier, 2019)
This dataset is related to the research article entitled “May iron(III) complexes containing phenanthroline derivatives as ligands be prospective anticancer agents?” [1]. It includes the characterization by UV–Vis absorption spectroscopy and magnetic techniques of a group of mixed ligand Fe(III) complexes bearing a tripodal aminophenolate ligand L2−, H2L = N,N-bis(2-hydroxy-3,5-dimethylbenzyl)-N-(2-pyridylmethyl)amine, and different aromatic bases (NN = 2,2′-bipyridine [Fe(L)(bipy)]PF6 (1), 1,10-phenanthroline [Fe(L)(phen)]PF6 (2), or a phenanthroline derivative co-ligand: [Fe(L)(amphen)]NO3 (3), [Fe(L)(amphen)]PF6 (3a), [Fe(L)(Clphen)]PF6 (4), [Fe(L)(epoxyphen)]PF6 (5) (where amphen = 1,10-phenanthroline-5-amine, epoxyphen = 5,6-epoxy-5,6-dihydro-1,10-phenanthroline, Clphen = 5-chloro-1,10-phenanthroline), as well as [Fe(L)(EtOH)]NO3 (6), [Fe(phen)Cl3] (7) and [Fe(amphen)Cl3] (8). Data on their hydrolytic stability in physiological buffers is shown, as well as on their interaction with calf thymus DNA by spectroscopic tools. Additionally, the anticancer efficacy and the cellular death mechanisms activated in response to these drugs in HeLa, H1299 and MDA-MB-231 cells are provided.
Keywords: Anticancer; Cytotoxicity; Fe(III) complexes; Genotoxicity; Phenanthroline